2017
DOI: 10.1108/mrr-07-2016-0160
|View full text |Cite
|
Sign up to set email alerts
|

Does the relationship between person–organization fit and work attitudes differ for blue-collar and white-collar employees?

Abstract: Purpose Most employee attitudes and behaviors are determined by both personal and situational characteristics. Studies on person–organization fit (POF), which is defined as the congruence between individual and organizational values, also support this assumption. Employees who perceive high POF have high positive work attitudes and low intention to leave. However, this study assumes that the relationship between perceived POF and work attitudes may be different with respect to employees’ status and aims to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 64 publications
1
14
0
2
Order By: Relevance
“…The results showed support for statistically negative relationships between personorganization fit and withdrawal behaviors, and an intention to leave in the sample of employees in the public university in Southern Thailand, leading to the conclusion that when employees perceive a good fit between themselves and the organization, their withdrawal behaviors are likely to decrease. This result emphasizes the importance of perceived personorganization fit from the employees' perspective, confirming the applicability of the personorganization fit theory outside the USA (Kim et al, 2013;Saraç et al, 2017). Specifically, the university from which the sample was drawn repeatedly emphasizes the value of dedication to the public.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…The results showed support for statistically negative relationships between personorganization fit and withdrawal behaviors, and an intention to leave in the sample of employees in the public university in Southern Thailand, leading to the conclusion that when employees perceive a good fit between themselves and the organization, their withdrawal behaviors are likely to decrease. This result emphasizes the importance of perceived personorganization fit from the employees' perspective, confirming the applicability of the personorganization fit theory outside the USA (Kim et al, 2013;Saraç et al, 2017). Specifically, the university from which the sample was drawn repeatedly emphasizes the value of dedication to the public.…”
Section: Discussionsupporting
confidence: 63%
“…Person-organization fit is defined as the match or congruence between individuals' values and the value of the organization in which they work (Lovelace and Rosen, 1996;Yaniv and Farkas, 2005). Numerous studies have investigated person-organization fit and have reported that when employees perceive a good fit between themselves and an organization, they become attached to that organization, leading to less stress, higher satisfaction and commitment, better work and other positive behaviors such as organizational citizenship behaviors, and a lower intention to leave an organization (Ahamed et al, 2013;Chernyshenko et al, 2009;Edwards and Billsberry, 2010;Jung and Yoon, 2013;Lovelace and Rosen, 1996;McShane and Von Glinow, 2010;Saraç et al, 2017;Yaniv and Farkas, 2005;Yaniv et al, 2010Yaniv et al, /2011. In this study, based on results from previous studies, person-organization fit was hypothesized to have a negative relationship with withdrawal behaviors and an intention to leave an organization: H1.…”
Section: Person-organization Fitmentioning
confidence: 99%
See 3 more Smart Citations